Hemophagocytic lymphohistiocytosis following gene replacement therapy in a child with type 1 spinal muscular atrophy. (4th August 2022) - Galletta, Francesca; Cucinotta, Ugo; Marseglia, Lucia; Cacciola, Annalisa; Gallizzi, Romina; Cuzzocrea, Salvatore; Messina, Sonia; Toscano, Antonio; Gitto, Eloisa
Abstract: What is known and objective: Onasemnogene abeparvovec (OA) is the first gene replacement therapy for the treatment of paediatric patients with bi‐allelic mutations in the SMN1 gene. Efficacy and safety of OA have been assessed in several studies with promising results, despite rare side effects have been described. Case summary: A 3‐year‐old child with spinal muscular atrophy was treated with OA and subsequently developed fever, widespread erythematous skin lesions and hepatosplenomegaly. Laboratory tests were suggestive for Hemophagocytic lymphohistiocytosis (HLH). What is new and conclusion: To our knowledge, this is the first case of HLH following gene replacement therapy with OA, described in literature.